Response Surface Method Based Optimization of the Viscosity of Waste Cooking Oil Biodiesel - Sedef Köse; Mustafa Babagiray; Tolga Kocakulak (Engineering Perspective)
In this study, biodiesel fuel production from waste sunflower oil and viscosity optimization was carried out. During the pro-duction process, catalyst ratio, alcohol ratio and reaction temperature were determined as variable parameters. Transesferication method was used as the production method. During the production process, the use of NaOH catalyst and methyl alcohol was provided. Biodiesel production steps with the transesterification method were discussed in detail. A total of 27 different biodiesel fuels were obtained with a catalyst ratio varying between 0.03% and 0.07%, alcohol content between 15% and 25%, and reaction temperature between 50 ° C and 70 ° C. All biodiesel fuels were analyzed and their characteristics were determined. In the opti-mization process, catalyst ratio, temperature and alcohol ratio were considered as input parameters, and viscosity as output pa-rameters.Both 3D surface plots and 2D contour plots were developed using MINITAB 19 to predict optimum biodiesel viscosity. To predict biodiesel viscosity a quadratic model was created and it showed an R2 of 0.95 indicating satisfactory of the model. Minimum biodiesel viscosity of 4.37 was obtained at a temperature of 60, NaOH catalyst concentration of 0.07% and an alcohol ratio of 25%. At these reaction conditions, the predicted biodiesel viscosity was 4.247. These results demonstrate reliable predic-tion of the viscosity by Response surface methodology(RSM).